Jogo, corpo e espaço: encontros de uma professora com a primeira infância - Deus, Roberta Liz de Queiroz Sousa de (2017)
This dissertation presents reflections on my pedagogical practice, involving corporeal experiences, with children from 4 to 5 years old. The practice, analyzed here, occurred in 2015, at a Municipal School of Early Childhood Education in the city of Uberlândia/MG. Through procedures based on the cartographic method, I tried to rethink my artistic trajectory and teacher training in order to find sources, pedagogical and artistic references that reverberated in my own analyzed teaching practice. One of the focuses of study, awakened by these references, was the way artists from various areas connect with young children. For the analysis of this aspect, as well as others raised during the research, audiovisual records and notes on the classes coordinated by me were analyzed. These classes involved playful procedures in children's bodily experience. From the analysis of the records, other topics, besides the way of establishing a connection, were raised, being also related to the previous references revisited. Among these themes are: play as its own territory or as performance and its appropriation by children; the presence of chance in meetings; as well as the way of sharing the experience that approached the developed process.